Influence of randomly distributed magnetic nanoparticles on surface superconductivity in Nb films - Stamopoulos, D.; Pissas, M.; Karanasos, V.; Niarchos, D.; Panagiotopoulos, I. (PHYSICAL REVIEW B, 2004)
We report on combined resistance and magnetic measurements in a hybrid structure (HS) of randomly distributed anisotropic CoPt magnetic nanoparticles (MN) embedded in a 160 nm Nb thick film. Our resistance measurements exhibited a sharp increase at the magnetically determined bulk upper-critical fields H-c2(T). Above these points the resistance curves are rounded, attaining the normal state value at much higher fields identified as the surface superconductivity fields H-c3(T). When plotted in reduced temperature units, the characteristic field lines H-c3(T) of the HS and of a pure Nb film, prepared at exactly the same conditions, coincide for H<10 kOe, while for fields H>10 kOe they strongly segregate. Interestingly, the characteristic value H=10 kOe is equal to the saturation field H-sat(MN) of the MN. The behavior mentioned above is observed only for the case where the field is normal to the film's surface, while it is absent when the field is parallel to the film. Our experimental results suggest that the observed enhancement of surface superconductivity field H-c3(T) is possibly due to the not uniform local reduction of the external magnetic field by the dipolar fields of the MN.